The Study of Religion and the Training of Muslim Clergy in Europe Academic and Religious Freedom in the 21st Century - Drees, Willem (LUP Academic, 2007)
Religious scholarship can be offensive to believers, as conflicts from the time of Galileo and Spinoza to the recent critique of Danish religious scholars in the wake of the infamous Muhammad cartoons have shown. Studies of this type of scholarship have been appropriated by believers as a means of reinventing their own identities - as the training of twentieth-century Muslim clergy demonstrates. This volume offers a unique collection of training materials from European Muslim clergy since the 1940s - including Third Reich reports on debriefing imams, surveillance files on Muslim activists, and information on Bosnian clergy and their training centres - as well as an exploration of religion and academic freedom in general, accompanied by appendices in both Arabic and English.